Accompaniment Model of Integrative Creative Economic for Tax Compliance - Susyanti, Jeni; Aminah, Siti (Economics and Business Solutions Journal, 2019)
Taxation is the primary source of income for a state. The purpose of this research to know the model of creative economic assistance, identification of income share, tax training action. This research includes descriptive research using qualitative methods. To analyze the data of researchers using Miles and Huberman theory through data reduction, data presentation, draw conclusions. The result of the research shows that it is necessary to assist the business of the creative economy in the field of accounting and taxation in integrative model. There is a share of revenue earned. Action expansion of tax training, to improve taxpayer compliance. The model test is done by analysis on an aspect of recording, business bookkeeping, fulfillment of tax obligation. A quad helix action model is required for creative economic assistance.
Keywords: integrative model; creative economic; tax complience